2020
DOI: 10.1002/smll.202006279
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlled Growth of Sub‐Millimeter 2D Cs2SnI6 Nanosheets at the Liquid–Liquid Interface

Abstract: Cs2SnI6 perovskite displays excellent air stability and a high absorption coefficient, promising for photovoltaic and optoelectronic applications. However, Cs2SnI6‐based device performance is still low as a result of lacking optimized synthesis approaches to obtain high quality Cs2SnI6 crystals. Here, a new simple method to synthesize single crystalline Cs2SnI6 perovskite at a liquid–liquid interface is reported. By controlling solvent conditions and Cs2SnI6 supersaturation at the liquid–liquid interface, Cs2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…To synthesize high-quality crystals, we first reported a solution-based method to grow single-crystalline Cs 2 SnI 6 at the liquid−liquid interface by dissolving two reagents (CsI and SnI 4 ) into two immiscible solvents. 48 Due to the immiscible nature of the two solvents, the precipitation of Cs 2 SnI 6 is constrained at the interface. By controlling solvent conditions and Cs 2 SnI 6 supersaturation at the liquid−liquid interface, Cs 2 SnI 6 crystals can be obtained with controlled geometries such as triangle, hexagon, truncated tetrahedron, and octahedron (see Methods; Figure S1, Supporting Information).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To synthesize high-quality crystals, we first reported a solution-based method to grow single-crystalline Cs 2 SnI 6 at the liquid−liquid interface by dissolving two reagents (CsI and SnI 4 ) into two immiscible solvents. 48 Due to the immiscible nature of the two solvents, the precipitation of Cs 2 SnI 6 is constrained at the interface. By controlling solvent conditions and Cs 2 SnI 6 supersaturation at the liquid−liquid interface, Cs 2 SnI 6 crystals can be obtained with controlled geometries such as triangle, hexagon, truncated tetrahedron, and octahedron (see Methods; Figure S1, Supporting Information).…”
Section: ■ Resultsmentioning
confidence: 99%
“…To synthesize high-quality crystals, we first reported a solution-based method to grow single-crystalline Cs 2 SnI 6 at the liquid–liquid interface by dissolving two reagents (CsI and SnI 4 ) into two immiscible solvents . Due to the immiscible nature of the two solvents, the precipitation of Cs 2 SnI 6 is constrained at the interface.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the stoichiometric CsI3-terminated (111) surface consistently has the lowest surface energy, indicating that it is the most thermodynamically favored surface among the seven terminations, in agreement with the recent experimental reports. [25][26] 3 Conclusion…”
Section: Fig 4 Illustration Of the Accessible Chemical Potential Region For Cs2sni6mentioning
confidence: 98%
“…Xu et al [24] reported a general approach to synthesize layered nanoplatelets of Cs2SnI6. Zhu et al [25] revealed that Cs2SnI6 crystals have a preferential growth of (111) surface. Several experiments also found that Cs2SnI6 tends to grow along the <111> direction [26][27][28] .…”
mentioning
confidence: 99%
“…Interestingly, a tiny drop of water, 0.2% (v/v), instantly changed the emission color from blue-green to a highly emissive green, which is in line with what we will discuss later. It is anticipated that the interaction of perovskite NCs with an extremely small amount of water leads to chemical dissolution, 43 formally releasing the constituent ions of FAPbBr 3 (FA + , Br − , Pb 2+ ) from the surface. Notably, the dissolution seems to take place at preferential sites instead of exhibiting a uniform dissolution of the crystal (Figures S8 and S9).…”
Section: Structural Propertiesmentioning
confidence: 99%